Micro-Ethnography Approach in Using Technology to Support Learning Interaction - Nandes, Yogi Novario; Triastuti, Anita; Priyana, Joko (Institut Agama Islam Negeri Palopo, 2025)
Technological and Artificial Intelligence (AI) development provides challenges and opportunities for lecturers to create dynamic and relevant classroom engagements, especially in courses that demand intensive communication skills, such as English Education. A micro-ethnography approach can help lecturers analyze social engagements in the classroom in detail, adapt their teaching style, and increase student engagement by combining technology and a personal approach. This study aims to explore lecturers' strategies for strengthening classroom interaction in English Education study program using the micro-ethnography approach in the era of technology and AI. This research uses the literature review method and qualitative descriptive analysis to collect and analyze data on lecturers' strategies for strengthening classroom interaction in the era of AI and technology in English language teaching. The results of this study show that the utilization of technology and the micro-ethnography approach in education, including in the English Education study program, is crucial to strengthen classroom interaction in the digital era. Technologies such as AI provide opportunities to understand students' learning preferences more personally, while micro-ethnography approaches help lecturers create inclusive and adaptive learning experiences. Keywords: AI; Learning Interaction; Micro-Ethnography; Technology